An Automated Approach for Execution Sequence-Driven Software and Physical Co-Design of Mechatronic Systems Based on Hybrid Functional Ontology. (February 2021) - Cao, Yue; Liu, Yusheng; Ye, Xiaoping; Zhao, Jianjun
Abstract: Most mechatronic systems have becoming software-intensive. Even in their early design, the software and physical domains intersect with each other deeply. It is significant to capture and process the cross-domain influences automatically to avoid design defects in late stages. Semantic web technologies have been recognized as effective enabling technologies to support cross-domain knowledge representation and inference. However, how to correlate the knowledge of software and physical designs, which have divergent characteristics in an ontological knowledge is the difficulty. In this study, with the help of semantic web technologies, an automated software-physical co-design approach is proposed based on a hybrid function ontology, which unifies the physical-centric flow-based functional representation and software-centric data/control flow diagram. Software and physical designs are linked to this unified functional ontology such that the execution sequences controlled by software can constrain the physical design and the updates on the execution sequences introduced by physical design can be reflected on software behaviors. An ontology-based framework is implemented to support this approach. Two case studies from different application areas are illustrated to show its effectiveness. Highlights: A hybrid functional ontology is proposed to unify multi-domain functional representations. Software and physical designs are correlated by ontologies defined in OWL2 DL. Physical structures are automatically evaluated against the execution sequences of functions. Software behaviors are automatically generated according to system functions. The approach is illustrated in two case studies from different application areas.